The Utilization Lizardfish As Base Material for Fish Jelly Processing With Arrrowroot Starch Addition - Putut Har Riyadi (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2006)
Processing of lizardfish (Saurida tumbil) for fish jelly product one of alternative product diversification that expect to be an acceptable product to the society. In Japan, Lizardfish has become generally used as raw material for producing fish jelly product. Meanwhile, arrow roots starch is considered to be the best choice for alternative substitute material of wheat in large scale. This research was aimed to observed the proper heating temperature and concentration of arrowroot starch and effect of the period of storage on quality of the fish jelly product. The research using laboratoriy experimental method. The result showed that different concept  of  arrowroot starch gave significant  effect on the gel strength,  elasticity, WHC, whiteness,  expcep  for  pH,  folding  test  (p<0,05).  The  concentration  of  arrowroot  starch  (10%)  gave highest gel strength on optime heat temperature 90 oC. The lenght of storage had significant effect to the quality  of  fish  jelly  product.  The  longer  the  storage  time  to  be  held,  lower  the  value  gel  strength, elasticity, WHC, whiteness and folding test.   Key words : Lizardfish, fishjelly product, arrowroot starch